Fenomena Gagal Bayar Pinjaman Online: Analisis Tanggung Jawab Para Pihak dalam Perspektif Hukum Perikatan - Adhwa Fadhiyah; Rifa Aulia Ramadani; Putri Aulia Azahra (PT. Saha Kreasi Indonesia, 2026)
The rapid development of financial technology (fintech), particularly peer-to-peer (P2P) lending services, has significantly reconfigured public access to financing through faster, more inclusive, and platform-based digital mechanisms. However, alongside this expansion, a structural issue has emerged in the form of the increasing incidence of loan defaults, which cannot merely be regarded as a debtor's breach of contract within the framework of conventional civil law. This study aims to examine the legal construction of the relationships among the parties involved in online lending services and to analyze the distribution of legal responsibility among lenders, borrowers, and platform operators from the perspective of the law of obligations. This research employs a normative legal research method using both the statutory approach and the conceptual approach, supported by descriptive-qualitative analysis of primary, secondary, and tertiary legal materials. The findings reveal that legal relationships in fintech lending are not merely bilateral but instead constitute a tripartite legal framework that requires a reassessment of the conventional concept of breach of contract. Platform operators cannot be viewed solely as administrative intermediaries; rather, they bear normative responsibilities relating to the principles of prudence, information transparency, and systemic risk management, while lenders and borrowers remain bound by the contractual obligations established under the law of obligations. Furthermore, existing academic studies have primarily focused on consumer protection and regulatory aspects, leaving the distribution of legal responsibilities among the parties insufficiently explored. This study concludes that a conceptual reconstruction of legal relationships in fintech lending is necessary to provide a more balanced framework of legal certainty in addressing loan default cases in Indonesia.